Percutaneous transhepatic and transseptal dilatation of a surgically implanted Melody® Valve in the mitral position in a 2-year-old child - Leticia Albert De La Torre; Belen Toral Vázquez; Dolores Herrera Linde; Alberto Mendoza Soto; Enrique García Torres (Wolters Kluwer Medknow Publications, 2022)
The use of the Melody® (Medtronic, Minneapolis, MN, USA) biological prosthesis in mitral position has shown acceptable short-term results. Furthermore, it allows its expansion with a balloon when the patient grows up, and this procedure can be performed by a venous catheterization through transseptal approach through an interatrial communication or puncturing the septum. Patients with complex congenital heart disease undergoing multiple surgical and percutaneous interventions may present with vascular complications such as thrombosis of the femoral venous system that make percutaneous access impossible. In this situation, the transhepatic approach is a very useful alternative to access the heart.